Spanish Themes in the Work of Natalia Goncharova - T. M. Maksimyuk (Ибероамериканские тетради)
Many research papers examine the artistic heritage of the Russian painter Natalia Goncharova, yet relatively few analyze the Spanish themes in her work that she first explored in her sketches for ballets inspired by Spain and then in a series of paintings known as «The Spaniards» («Las españolas»). Nonetheless, in 1939, in the artist’s lifetime, an exhibition «Natalia Goncharova: Spaniards and magnolias» was held at the French gallery «Le Cadran». Marina Tsvetayeva, Russian poet and prose writer, described «The Spaniards» in her essay «Natalia Goncharova: Life and Work», highlighting the distinctive features of this series of paintings. These include the musical rhythm of contours and colour combinations, ethnographic elements, repetitive motifs, at the same time the variety of their interpretation, since the painter’s style evolved from decorative cubism to Art Deco and neoclassicism. Works with Spanish themes play an important role in Natalia Goncharova’s art because the images she created from 1916 to the early 1940s, during her Parisian period, reminded her of the homeland she had left. Thus, the study of the evolution of style, technique and function of Spanish themes helps to not only evaluate the influence of the theatre and flamenco on this series of works, but also to identify its two key components, namely the folkloric and the aristocratic. Combining the Western form of Spanish images with their Eastern spirit, Natalia Goncharova underlined the similarities between Russian and Spanish culture.